Thermal analysis and energy requirement of wall and window components for buildings with different orientations - Ozel, Meral; Sengur, Serhat (Yildiz Technical Univ, 2025)
This research highlights the importance of wall insulation, type of glazing and glazing area to reduce energy consumption and to ensure thermal comfort in residential buildings. With the appropriate combination of design parameters such as window glass area, glazing type, wall orientation and wall insulation, heating and cooling loads and therefore energy requirements can be substantially reduced. The main goal of this research is to analyze the thermal performance and energy requirements of the wall and window components that can make residential buildings energy efficient, considering building orientations for four cities of T & uuml;rkiye. Firstly, heat gain and losses through walls and windows are numerically researched. The heat transmission loads through wall are computed employing an implicit finite difference procedure. Secondly, the ratio of window to wall area is also investigated from the transmission loads point of view. Then, heating and cooling energy requirements and costs are also separately determined for walls consisting of single and double-glazed windows. Consequently, it is observed that the orientation, climate conditions, geographical location, type of glazing and insulation have a notable effect on heat transmission and energy requirement. The results also show that the highest heating energy requirement and cost are acquired for the north orientation in Kars, where the heating load is dominant while the highest cooling energy requirement and cost are acquired for the west (or east) orientation in Antalya, where the cooling load is dominant. It is revealed that the double glazing significantly reduces these energy requirements. The results show that this reduction in heating need for Kars is 61.91%, 45.81%, 49.01% and 49.01% for South, North, East and West orientations, respectively. On the other hand, it is seen that this decrease in cooling need for Antalya is 30.45%, 33.30%, 25.17% and 25.17%. Also, the double glazing appears to be more effective at reducing heating demand than at reducing cooling demand. The results acquired in this work will be very beneficial in the selection of glass type and the glazing area, taking into account the wall direction, when designing exterior walls of residential buildings in different climatic zones.
Keywords: Climate Zones; Energy Requirements; Heat Gain and Losses; Noninsulated Wall and Insulated Wall; Single-Glazing and Double-Glazing